Strained topological insulator spin field effect transistor. (3rd March 2023) - Bandyopadhyay, Supriyo
Abstract: The notion of a spin field effect transistor, where transistor action is realized by manipulating the spin degree of freedom of charge carriers instead of the charge degree of freedom, has captivated researchers for at least three decades. These transistors are typically implemented by modulating the spin orbit interaction in the transistor's channel with a gate voltage, which causes gate-controlled spin precession of the current carriers, and that modulates the channel current flowing between the ferromagnetic source and drain contacts to implement transistor action. Here, we introduce a new concept for a spin field effect transistor which does not exploit spin-orbit interaction. Its channel is made of the conducting surface of a strained three dimensional topological insulator (3D-TI) thin film and the transistor function is elicited by straining the channel region with a gate voltage (using a piezoelectric under-layer) to modify the energy dispersion relation, or the Dirac velocity, of the TI surface states. This rotates the spins of the carriers in the channel and that modulates the current flowing between the ferromagnetic source and drain contacts to realize transistor action. We call it a strained-topological-insulator-spin-field-effect-transistor, or STI-SPINFET. Its conductance on/off ratio is too poor to make it useful as a switch, but it may have other uses, such as an extremely energy-efficient stand-alone single-transistor frequency multiplier.